MEMBANGUN KINERJA GURU BERLANDASKAN NILAI-NILAI AGAM ISLAM - Eny Suryani (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
In Islam, learning is compulsory. Then in the learning process, Islam provides guidance. It is intended that learning impacts and makes learners nobel. Among the guidelines are patience, commitment, and consistency based on worship. Then the impact of that is sincerity (enjoying learning). For teachers continuous learning is a necessity. Certainly getting a method that is detailed and guaranteed will make it a trustworthy person in educating results-oriented and life benefits (quality). This research was conducted to see how the performance of teachers through the practice of Islamic religious values, whether realized or not. The research method uses a qualitative approach using the interview method and the closed answer scale. The object of this research is a state junior high school in South Tangerang City. The sampling technique uses judgment sampling. The results of the study suggest that the teacher feels emotionally bound by the spiritual which is always practiced to be a good teacher (quality)